PERAN ORANG TUA DALAM MEMBENTUK IDENTITAS AGAMA ISLAM PADA ANAK USIA DINI - Hidayah, Choirul; Rohman, miftakhul (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
Religion is something that is very important for every human being to have. Instilling religious values ​​must start from an early age. The role of parents is very influential in the formation of religious values ​​in children. Educational Institutions as a forum for solutions for parents who are unable to nurture and educate their children well. TAB Syuhada' Haji is one of the Islamic Education Institutions which operates in the field of early childhood education. As for the qualitative approach, data was collected from in-depth interviews, observations and documentation at KB TAB Syuhada Haji, Blitar. The research results show that parents play a strategic role through example, habituation, direct education, and creating an Islamic environment. Supporting factors include a good understanding of religion and sufficient time, while inhibiting factors include busy parents and the influence of modern media. Integrative strategies involving religious education at home and school have proven effective in forming the character of children who are faithful and devout. This research recommends an Islamic parenting approach that is relevant to facing the challenges of the modern era.